PENGEMBANGAN MEDIA COMPUTER ASSISTED INSTRUCTION PADA MATA PELAJARAN FIQIH MATERI NAJIS BAGI SISWA KELAS VII DI MTs. BINA INSANI SURABAYA - Amalia Khoirunnisa', Ratna (Jurnal Mahasiswa Teknologi Pendidikan, 2016)
Abstrak Penelitian ini dilakukan untuk menghasilkan media Computer Assisted Instruction yanglayak dan efektif untuk digunakan dalam proses pembelajaran pada mata pelajaran fiqih materi najis. Kelayakan sebuah media ditunjukkan dari hasil wawancara ahli materi, ahli media dan angket. Media Computer Assisted Instruction juga dikatakan efektif apabila diadakannya sebuah tes yaitu dengan perbandingan pretest danposstest. Jika prestasi belajar pada siswa mengalami peningkatan, maka media Computer Assisted Instruction ini dikatakan efektif.Pengembangan media ini menggunakan model pembelajaran ADDIE (Analysis, Design, Development, Implementation, danEvaluation). Sasaran pengembangan dalam penelitian ini adalah siswa kelas VII di MTs Bina Insani Surabaya yaitu 30 siswa, dimana 3 siswa melakukan uji coba perorangan, 5 siswa melakukan uji coba kelompok kecil, dan 30 siswa melakukan uji coba kelompok besar. Penelitian ini merupakan jenis penelitian pengembangan, dimana metodenya terdapat perbandingan kelas kontrol dan eksperimen.Jika hasil uji coba kelas eksperimen meningkat dari kelas kontrol, maka pengembangan media ini membantu siswa dalam proses pembelajaran. Dalam proses pengembangan media Computer Assisted Instruction dilakukan dalam beberapa tahap seperti reviewahli materi I dan II, ahli media I dan II, uji coba perorangan, uji coba kelompok kecil dan uji coba kelompok besar. Pengumpulan data media Computer Assisted Intruction menggunakan metode wawancara dan angket untuk uji kelayakan, dan hasil tersebut dianalisis menggunakan rumus deskriptif presentase. Pengumpulan hasil data pretes dan postes di hitung menggunakan rumus t. Berdasarkan hasil data persentase ahli materi I dan II yaitu 90%, ahli media I dan II sebesar 90%, uji coba perorangan sebesar 88%, uji coba kelompok kecil92,85%, dan uji coba kelompok besar 94,76%. Dari hasil tersebut, dapat disimpulkan bahwa media Compter Asissted Instruction dikategorikan baik dan media ini layak untuk digunakan. Sedangkan hasil uji coba untuk penilaian efektifitas diperoleh thitung lebih besar dari ttabel yaitu 9,28 > 2,045. Sehingga dapat disimpulkan bahwa media Computer Assisted Instruction ini efektif untuk digunakan dalam pembelajaran. Kata kunci : Pengembangan, Media Computer Assisted Instruction, Materi Najis. Abstract This study was conducted to make a Computer Assisted Instruction media that feasible and effective for learning process on the subjects of Fiqh about odious theory. The feasibility of the media is showed from the results of expert interview, media experts and questionnaire. The effective Computer Assisted Instruction Media is if it was holding a test with comparison of pretest and posttest. If the learning achievements of students has increased, then the media Computer Assisted Instruction is said to be effective. The development of this media using the learning model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Target development in this research is VII grade of MTs Bina Insani Surabaya with the number of 30 students, where students the 3 of students perform an individual tests, 5 students did a test run in small groups, and 30 students doing a test in large groups. The kind of this study is research development, where there is a comparison of the control class and experiment class. If the results of experimental classes are increase than the control class, then this media development helps students in the learning process. In the process of developing a Computer Assisted Instruction media, it conduct in several stage that are expert review the material I and II, expert media I and II, individual trials, trials of small group and large group testing. The method that use for collecting data for Computer Assisted Instruction Media are using interview and questionnaire to testing the feasibility of this media, and the results are analyzed using descriptive percentage formula. The collection of data and results in the pretest and posttest are calculated by using the t formula. Based on the results matter experts percentage data I and II is 90%, media expert I and II by 90%, individual testing by 88%, test a small group 92.85%, and testing large groups of 94.76%. From these results, it can be concluded that the media CompterAsissted Instruction categorized as good and worthy to use this media. While the results of testing for effectiveness assessment obtained t is greater than t table ie 9.28> 2.045. It can be concluded that the media Computer Assisted Instruction is effective for use in learning. Keyword : Development, Computer Assisted Instruction Media, Unclean Material. This study was conducted to make a Computer Assisted Instruction media that feasible and effective for learning process on the subjects of Fiqh about odious theory. The feasibility of the media is showed from the results of expert interview, media experts and questionnaire. The effective Computer Assisted Instruction Media is if it was holding a test with comparison of pretest and posttest. If the learning achievements of students has increased, then the media Computer Assisted Instruction is said to be effective. The development of this media using the learning model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Target development in this research is VII grade of MTs Bina Insani Surabaya with the number of 30 students, where students the 3 of students perform an individual tests, 5 students did a test run in small groups, and 30 students doing a test in large groups. The kind of this study is research development, where there is a comparison of the control class and experiment class. If the results of experimental classes are increase than the control class, then this media development helps students in the learning process. In the process of developing a Computer Assisted Instruction media, it conduct in several stage that are expert review the material I and II, expert media I and II, individual trials, trials of small group and large group testing. The method that use for collecting data for Computer Assisted Instruction Media are using interview and questionnaire to testing the feasibility of this media, and the results are analyzed using descriptive percentage formula. The collection of data and results in the pretest and posttest are calculated by using the t formula. Based on the results matter experts percentage data I and II is 90%, media expert I and II by 90%, individual testing by 88%, test a small group 92.85%, and testing large groups of 94.76%. From these results, it can be concluded that the media CompterAsissted Instruction categorized as good and worthy to use this media. While the results of testing for effectiveness assessment obtained t is greater than t table ie 9.28> 2.045. It can be concluded that the media Computer Assisted Instruction is effective for use in learning. Keyword : Development, Computer Assisted Instruction Media, Unclean Material.